2021
DOI: 10.1021/acs.inorgchem.0c03355
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Flower-like Fe-Doped CoO Nanocomposites with Dual Enzyme-like Activities for Facile and Sensitive Determination of H2O2 and Dopamine

Abstract: Herein, a new series of magnetic Fe-doped CoO nanocomposites (Fe-CoO NCs) with dual enzyme-like activities (peroxidase and oxidase) were successfully synthesized. The molar ratio of Fe3+/Co2+ salts during the solvothermal process determined the morphology and catalytic activity of the NCs. Among them, the flower-like 0.15Fe-CoO NCs showed high peroxidase-mimicking activity over a wider pH range of 4–5 and a temperature range of 30–50 °C. Such nanozymes were applied for constructing a facile and sensitive color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…It can be seen from the figure that the CoO nanoparticles prepared at 270 • C had a higher POD-like catalytic activity. More importantly, we did not observe an SOD-like catalytic activity on CoO nanoparticles prepared at 320 • C. Some of the literature mentions that flower-like nanozymes will show a higher enzyme-like catalytic activity due to their larger specific surface area [53]. Based on this, we speculate that the change in the catalytic activity of the enzyme-like enzymes after the change in the morphology of CoO nanozymes is also derived from the change in the specific surface area and the opening of surfactant sites.…”
Section: Properties Of Coo Nanoparticlescontrasting
confidence: 59%
See 3 more Smart Citations
“…It can be seen from the figure that the CoO nanoparticles prepared at 270 • C had a higher POD-like catalytic activity. More importantly, we did not observe an SOD-like catalytic activity on CoO nanoparticles prepared at 320 • C. Some of the literature mentions that flower-like nanozymes will show a higher enzyme-like catalytic activity due to their larger specific surface area [53]. Based on this, we speculate that the change in the catalytic activity of the enzyme-like enzymes after the change in the morphology of CoO nanozymes is also derived from the change in the specific surface area and the opening of surfactant sites.…”
Section: Properties Of Coo Nanoparticlescontrasting
confidence: 59%
“…CoO nanozymes with three types of enzyme catalytic activities have not been reported yet, and most CoO nanozymes only have oxidase-/peroxidase-like catalytic activity [53]. A single enzyme-like catalytic activity greatly limits the application of CoO nanozymes in the biomedical field, so CoO nanozymes with multiple types of enzyme-like catalytic activities broaden their application scenarios.…”
Section: Enzyme-like Activity Determination Of Coo Nanozymesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Liu and Liu et al reported a new series of magnetic flower-like CoO nanocomposites (Fe–CoO NCs) doped with 0.15Fe, possessing peroxidase and oxidase dual enzyme mimetic activities for the rapid and selective chromogenic detection of H 2 O 2 and dopamine (DA) with an LOD of 4.40 and 1.99 μM, respectively. 164 The introduction of Fe herein was beneficial for the easy magnetic separation of the nanocomposite. Initially, the Fe 2+ in the doped Fe compounds was oxidized to Fe 3+ by decomposing H 2 O 2 to ˙OH, which then oxidized the chromogenic substrate TMB.…”
Section: Exploration Of Different Types Of Zero-dimensional Nanomater...mentioning
confidence: 99%